Prediction of blue, red and green aurorae at Mars. (September 2015) - Lilensten, J.; Bernard, D.; Barthélémy, M.; Gronoff, G.; Simon Wedlund, C.; Opitz, A.
Abstract: The upper atmosphere of Mars is a laboratory for better understanding the planetary atmosphere evolution, and is an example of the interaction of the solar wind with an unmagnetized planet that has only patches of crustal magnetic field. In that context, several space missions were launched to study the Martian environment and its aurorae, notably ESA's Mars Express discovered the first aurora-like structures, and more recently NASA's MAVEN, which is dedicated to understand the atmospheric escape. However, none of the existing missions have spectrometers in the visible spectral range for the observation of the upper atmosphere and the aurorae, but there are UV spectrometer which can be used to infer visible aurora emission. The UV aurorae on Mars have a counterpart in the visible spectral range which should be detectable under the right conditions. We discuss what are the most favorable conditions to observe these aurorae discernible with the naked eye. In this paper, we simulate the Martian aurora in the visible spectral range both with an experimental setup (the Planeterrella, which we use to measure intensity with respect to the naked eye) and with a numerical ionosphere simulation model (Trans⁎/Aeroplanets). We show that the electron impact on CO2 produces strong emissions at 412 nm and 434 nm, i.e., in the blue part of the visible spectrum which are due to the CO2 + (A) Fox–Duffendack–Barker bands. The modeling of the electron transport at Mars shows that these blue emissions as well as the emissions of the 630 nm (red) and 557.7 nm (green) lines of atomic oxygen may be observable several times during a solar cycle during strong solar events. The absence of visible spectrometers dedicated to these observations onboard existing space missions and the location of the different Martian rovers, far from the vertically aligned crustal magnetic field lines of Mars, have prevented so far the observations of such an aurora. In the foreseeable future, two missions may help observing these aurorae: the exo-Mars/Trace Gas Orbiter mission will carry a visible spectrometer which could be used to detect these events in the visible spectral range. NOMAD (Nadir and Occultation for Mars Discovery) will carry a UV-visible spectrometer in the 200–650 nm range. Abstract : Highlights: First prediction of blue, red and green auroras at Mars. Determination of the occurrences and locations of the Mars visible aurora. These Mars visible auroras could be seen with naked eyes. First prediction of visible auroras on a telluric planet other than the Earth.